Symbolic Figures of Speech in the Lyrics of the Song Kolam Susu by Koes Plus - Yesi Fitria; Annisa Putri Andini; Bunga Ivanny Marsya; Karlia Marhamatur Robaaniyya; Encep Kusumah (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
Koes Plus is a music band that was once established in Indonesia which was formed in 1969, this music group is widely known as one of the pioneers of pop and rock and roll genre songs in Indonesia, as well as one of the most productive and longest-standing music groups. "Kolam Susu" is a song created by Yok Koeswoyo and sung by the music group Koes Plus and first appeared on the album Volume 8 in 1973. This study aims to facilitate listeners in understanding the meaning contained in the song Kolam Susu through the analysis of symbolic figures of speech contained in the song lyrics. This study uses a descriptive method based on a qualitative approach with the main data source in the form of the song lyrics Kolam Susu. The data of this study, namely written song lyrics as a data source, were collected using observation guidelines with time triangulation techniques through a checklist. The analysis technique is based on clause language units to identify the symbolic figures of speech used. The results of the study revealed that there are six clauses in the song Kolam Susu that contain symbolic figures of speech, which play an important role in conveying meaning implicitly and enriching the song's message. This finding shows that symbolic figures of speech are effectively used as a tool to facilitate listeners in capturing deep meaning in song lyrics. This study is expected to contribute to the study of semantics and appreciation of Indonesian music.